STRATEGY TO IMPROVE THE QUALITY OF ISLAMIC SERVICES TO CUSTOMERS AT INDONESIA SHARIA BANK (BSI) IN JAMBI - Kurnia, Arya Aji; Rafidah (Journal of Management and Islamic Finance, 2023)
This study aims to find out how the strategy is to improve the quality of Islamic services contained in Indonesia Sharia Bank for its customers during the Covid-19 period in Jambi. The research method was field research using qualitative in nature, data collection used three techniques, namely observation, interviews, and documentation and was carried out on December 13, 2021 at Indonesia Sharia Bank, Jambi. The results of the research strategy to improve the quality of Islamic services to customers of Indonesia Sharia Bank in Jambi and in accordance with the concept of Ultimate Service as Business Acceleration have been running optimally in accordance with the 6 dimensions of service quality described by Othman and Owen known as the CARTER method, (Compliance, Assurance, Responsiveness, Tangible, Empathy and Reliability). Principles of Islamic law do not cheat and always provide financial solutions.